Lifetime estimation of single crystal macro-fiber composite-based piezoelectric energy harvesters using accelerated life testing. (October 2021) - Peddigari, Mahesh; Kwak, Min Sub; Min, Yuho; Ahn, Cheol-Woo; Choi, Jong-Jin; Hahn, Byung Dong; Choi, Cheol; Hwang, Geon-Tae; Yoon, Woon-Ha; Jang, Jongmoon
Abstract: Piezoelectric energy harvesters (PEHs) based on single crystal macro fiber composites (SFCs) have been widely utilized in vibration sensing, energy conversion, and power portable/wearable electronic devices. Despite growing attention to improve the output power of PEHs, few dedicated studies on reliability, especially on estimation of the usable lifetime of PEHs, have been reported. In this paper, an accelerated life test is applied to d 32 -type hard SFC-based PEHs to efficiently estimate usable lifetime in a short period of time. High temperature is used as environmental stress to accelerate the life of the PEHs, and time-to-failures are collected according to the criterion of a 10% drop in output power at 45, 55, and 70 °C under a mechanical vibration of 4.9 m/s 2 . The statistical failures distribution is analyzed using the Arrhenius-Weibull model with an activation energy ( E a ) of 2.36 eV and a shape parameter ( β ) of 1.44. Accordingly, the average lifetime to failure of the PEHs in normal use ( i.e., at room temperature) is determined as 4.3 × 10 9 vibration cycles. In addition, each failure mode is assessed to identify vulnerable points that reduce the lifespan of SFC-based PEHs. This study provides insight for evaluating and enhancing the reliability of PEHs as a basis for future practical application. Graphical Abstract: This work demonstrates the usable lifetime estimation of the single-crystal macro fiber composite-based piezoelectric energy harvester using accelerated life test method for the first time by performing the fatigue evaluation at high-temperature stress conditions and extrapolating the life-stress relation to normal use condition. ga1 Highlights: The accelerated life test method is used to estimate the usable lifetimes of SFC-based piezoelectric energy harvesters. The failure site and mode of the piezoelectric energy harvesters are systematically analyzed. Temperature-dependent lifetime behavior of piezoelectric energy harvesters under cyclic mechanical loading is investigated.